Development Strategy of Biomass Economy in China - Tian Yishui (《中国工程科学》杂志社, 2021)
Developing biomass economy is conducive to economic growth and rural development; it reduces fossil energy consumption and improves ecological environment. Biomass economy has great development potentials, but it still faces various challenges. In this article, the biomass resources in China are comprehensively analyzed, the industry and its current situation and trend are evaluated, and the strategic objectives, key projects, and policy suggestions for industrial development are proposed. China is rich in biomass resources, and biomass briquette fuel, large-scale biogas engineering, biomass power generation and cogeneration technologies are mature. These technologies have exhibited a good momentum of large-scale development and will be the main utilization approaches for a period of time in the future. The development idea proposed in this article for the biomass economy in China regards each county-level region as a unit and considers regional resource endowment, economic development level, and industrial development requirements. The development goals of the biomass economy in China are clarified as becoming mature, system innovation, and large-scale replacement by 2025, 2035, and 2050, respectively. Furthermore, policy suggestions are proposed in terms of technology research and development, incentive policy, market cultivation, and capital investment.